EFFECTS OF LIVE AND MICROENCAPSULATED FOOD ON THE GROWTH AND SURVIVAL OF COLOSSOMA MACROPOMUM CUVIER, 1816 (CHARACIFORMES, SERRASALMIDAE) POSTLARVAE - Alvarez-Verde, Claudio (2021)
In aquaculture, the survival of fish postlarvae is influenced by food. The gamitana, Colossoma macropomum Cuvier, 1816, is a species of great economic importance in our country. In the present work, the growth of gamitana C. macropomum postlarvae was evaluated, subjected to three feeding treatments: T1, live food composed of brine shrimp nauplii; T2, food composed of brine shrimp nauplii plus microencapsulated experimental food and T3, only microencapsulated experimental food. Food was provided "ad libitum" and postlarvae growth, specific growth rate, weight gain and survival rate were evaluated. The microencapsulated food was prepared by the gelling, drying and grinding technique. The experiment lasted 30 days. 450 gamitana postlarvae with initial average size of 0.02 ± 0.012 cm distributed in nine aquariums were used. The experimental design was completely randomized with three treatments and three replications per treatment. The results showed significant differences between the treatments for weight gain (g), the specific growth rate (%) and survival (%). For T : 1.25 g; 13.93% and 1 70.66%; for T : 1.38 g; 14.23% and 78%; for T : 0.83 g; 13.48% and 56.66%, respectively. The water 2 3 quality parameters were within the appropriate ranges for the species. It is concluded that the best yields were obtained with the T2 treatment, brine shrimp nauplii plus microencapsulated food.